2021
DOI: 10.3389/fphar.2021.654319
|View full text |Cite
|
Sign up to set email alerts
|

Ig Glycosylation in Ulcerative Colitis: It’s Time for New Biomarkers

Abstract: Background: Ulcerative colitis (UC) is a chronic relapsing disease, which needs a continue monitoring, especially during biological therapies. An increasing number of patients is treated with anti-Tumor Necrosis factor (TNF) drugs, and current research is focalized to identify biomarkers able to monitor the disease and to predict therapeutic outcome.Methods: We enrolled consecutive UC patients treated with anti-TNF, naïve to biologic drugs. Therapeutic outcome was evaluated after 54 weeks of treatment in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…MGAT5 genetic variants were described to influence plasma IgG glycome composition in UC patients, particularly with agalactosylation of IgGs Fc, correlated with a pro‐inflammatory phenotype [132]. Moreover, the Fc N ‐glycosylation profile of IgGs, particularly lower IgG galactosylation levels, were associated with IBD clinical features, such as more extensive and progressive disease [158] and with clinical and endoscopic activity in UC patients [159]. Treatment with biologics, such as anti‐TNF therapy was described to increase IgG Fc galactosylation [159].…”
Section: Role Of Glycans In the Breach Of Immune Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…MGAT5 genetic variants were described to influence plasma IgG glycome composition in UC patients, particularly with agalactosylation of IgGs Fc, correlated with a pro‐inflammatory phenotype [132]. Moreover, the Fc N ‐glycosylation profile of IgGs, particularly lower IgG galactosylation levels, were associated with IBD clinical features, such as more extensive and progressive disease [158] and with clinical and endoscopic activity in UC patients [159]. Treatment with biologics, such as anti‐TNF therapy was described to increase IgG Fc galactosylation [159].…”
Section: Role Of Glycans In the Breach Of Immune Tolerancementioning
confidence: 99%
“…Moreover, the Fc N ‐glycosylation profile of IgGs, particularly lower IgG galactosylation levels, were associated with IBD clinical features, such as more extensive and progressive disease [158] and with clinical and endoscopic activity in UC patients [159]. Treatment with biologics, such as anti‐TNF therapy was described to increase IgG Fc galactosylation [159]. IgG Fc glycosylation profile was found to be able to discriminate between UC, CD and healthy controls [158,160].…”
Section: Role Of Glycans In the Breach Of Immune Tolerancementioning
confidence: 99%
“…Low mucosal IL23 expression at baseline relates to UST treatment resistance [33]. Glycosylation experiments performed in the serum of patients with UC revealed that certain glycan structures exposed in the immunoglobulins might predict the response to infliximab (IFX) or ADA [34]. Similarly, the classification of IBD patients according to their basal circulating levels of nicotinamide phosphoribosyltransferase (NAMPT) discriminates with high sensitivity and specificity for the patients that will benefit from ADA treatment [35].…”
Section: Blood and Intestinal Tissue Biomarkersmentioning
confidence: 99%